Herbívoros de médio e grande porte do Cerrado: influência na ecologia de plantas e comportamento de forrageio - Marina Peres Portugal (2012)
Vertebrate herbivores feeding on flowers and fruits can alter the balance between vegetative growth and plant reproduction. In the Brazilian Cerrado, fire can act in this process attracting herbivores to burned areas and influencing plant reproduction. An herbivores foraging behavior may also influence on herbivory effect size. This work aims to analyze fire and herbivores influence in the Cerrados herbs reproduction and analyze the pampas deer (Ozotoceros bezoarticus) foraging behavior at the Emas National Park (ENP). To my knowledge, this is the first study about the effects of South American native ungulate herbivory. In order to study this, exclosures and track stations were installed and individuals of pampas deer were accompanied during its foraging. The studied areas were visited by medium and big sized herbivores, but no difference was found between burned and unburned areas. Two plant species were negatively affected by herbivory, Campomanesia adamantium and Manihot tripartita. Fire influenced positively on Dimerostemna brasilianum and M. tripartita bud and flower production. It also affected the seed average weight of the former species. Pampas deer foraging responded to food availabity in the patches. The pampas deer ingested on average 25,8% of all M. tripartita resources (buds, flowers and fruits) and 51,4% of fruits only. Patch depletion was a rare event. The decision of foraging on the patch was strictly related to the number of fruits. Pampas deer foraging had pattern similar to the type I functional response. This is an uncommon response of an herbivore, but it may be associated , to the small size of the fruit and its limited quantity. The size of the Cerrados herbivores, its foraging behavior and the high vegetal diversity of Cerrado can be associated to the herbivory low intensity found in this work. Fire seems to be a more important factor in these herbs vegetal dynamics than herbivory.